Responses of Vitis vinifera L. cv. Sultanina to Level of Soil Water Depletion Under Semi-Arid Conditions - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
Sultanina grapevines were irrigated at 90%, 60% and 30% plant-available water (PAW) depletion during the growing season in a field trial on a fine sandy soil in the Lower Orange River region of South Africa. Grapevines of all treatments were irrigated at 60% PAW depletion during winter.  Measurement of diurnal leaf water potential (tJ'1) cycles at different stages during the season showed that plant water status was not only a function of soil water availability, but also of meteorological conditions. Increasing vapour pressure deficit (VPD) decreased pre-dawn leaf water potential, suggesting nocturnal water loss via transpiration. On the other hand, tpl measured at 14h00 increased with an increase in VPD, indicating partial stomatal closure during the warmest part of the day.  Vegetative growth, berry mass and production increased with increased plant water status as imposed by the different PAW depletion levels. PAW depletion level had almost no effect on sugar accumulation or acid breakdown.  Soil water depletion level had no effect on the quality of dipped raisins. Hence, the ideal balance between vegetative growth, yield and water use efficiency for the production of dipped Sultanina raisins was obtained with irrigation at 60% PAW depletion. Since quality of sun-dried raisins was considerably reduced by irrigation at 60% as well as 90% PAW depletion, relative to 30% depletion, the latter seems to be the optimum depletion level for sun-dried raisin production. This optimum depletion level might not be applicable for irrigation of Sultanina on heavier, more fertile alluvial soils.